Unsteady flow induced by variable suction on a porous disk rotating eccentrically with a fluid at infinity - A. K. Ghosh; S. Paul; Lokenath Debnath (International Journal of Mathematics and Mathematical Sciences)
We study the effect of variable suction or blowing on the flow of an incompressible viscous fluid due to noncoaxial rotations of a porous disk and a fluid at infinity. The inquiries are made about the components of fluid velocity and the shear stress at the disk. It is found that the effect of uniform suction or blowing on the flow is enhanced in the presence of variable suction or blowing.